2016
DOI: 10.1589/jpts.28.1892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise intervention on serum cartilage oligomeric matrix protein levels and lymphocyte DNA damage in obese elderly females

Abstract: [Purpose] The aim of the reported research was to investigate the effects of regular aerobic exercise on cartilage oligomeric matrix protein and oxidative DNA damage in obese, elderly females. [Subjects and Methods] Sixteen class I obese, elderly females, according to World Health Organization criteria, were randomly and equally assigned to a control group (n=8) or an exercise group (n=8). The exercise group participated in exercise sessions of 60 minutes per day, 3 days per week, for a period of 8 weeks. [Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We should focus on not only intervention method but also the period of appropriate therapeutic intervention. Three recent studies have demonstrated that pre or early potential preventive effect on human and animal model studies 45 , 46 , 47 ) .…”
Section: Discussionmentioning
confidence: 99%
“…We should focus on not only intervention method but also the period of appropriate therapeutic intervention. Three recent studies have demonstrated that pre or early potential preventive effect on human and animal model studies 45 , 46 , 47 ) .…”
Section: Discussionmentioning
confidence: 99%